(untitled) (Movimento-revista de educação, 2020)
This paper presents a qualitative research examining the extent to which sojourns abroad engage their partakers in intercultural interactions and explores whether experiences like this translates into intercultural growth in students. The results of this study demonstrated that studying abroad would not suffice for complete immersion into the local community or allow one to discover the nuances of another culture in their entirety. Nonetheless, students who were surrounded by their local and international counterparts were exposed to foreign cultures and were motivated to explore and interpret the diversity they encountered. They were thus equipped with knowledge of unfamiliar cultures and were sensitised to cultural diversity. Such contact often challenged the students’ established opinions and ideas, which largely stemmed from stereotypes about specific cultures. Rethinking this, to varied extents, resulted in evolved attitudes and values. International engagement also stimulated introspection and a deepened understanding of identity among the students, thereby contributing to their self-awareness. By offering opportunities to experience cultural diversity, the sojourn prompts students to develop coping strategies and draw parallels with their own culture, along with fostering intercultural development to a certain degree, and is therefore of great significance for policy makers, curriculum developers, teachers and tertiary students.